DAMPAK PERKEMBANGAN CITY HOTEL TERHADAP USAHA HOTEL MELATI DI KOTA DENPASAR - Trisni Sakawati, Ketut Ngurah (Jurnal Master Pariwisata (JUMPA); Volume 02, Nomor 01, Juli 2015, 2015)
The tourism sector of Bali has developed rapidly in the last tenyears, especially when it is seen from the trend of the numbers ofdomestic and foreign tourist arrivals. This trend is accompaniedwith the increasing number of accommodation facilities. Denpasaris a region which shows the rapid growth of accommodationfacilities, such as the presence of a number of hotels in the city areawhich is often referred to as a city hotel. This study examines thefactors that cause the growth of city hotels, the impacts of the cityhotel growths on the budget hotel businesses, the competition andbusiness strategies of inter-city hotels as well as their influences onbusiness strategies of budget hotels in Denpasar City. The theoriesapplied in the study were the theory of supply and demand, theimpact theory and the theory of tourism policy. Data were collectedthrough observation and interviews with relevant tourismstakeholders. The findings show the rapid developments of the cityhotels have given negatif and positive impacts on the businesses ofthe budget hotels in Denpasar. To prevent excessive developmentof the city hotel, it is recommended to Denpasar government todevelop a needs assessment of hotel rooms and some policies suchas standard setting policies of room rates or equitable policy of thehotel developments.